Phosphines and N-heterocycles joining forces: an emerging structural motif in PNP-pincer chemistry - Merz, Lukas; Ballmann, Joachim; Gade, Lutz H. (European journal of inorganic chemistry, 2020)
Aminodiphosphines and their monoanionic amido derivatives are among the most widely used tridentate ligands. A good share of these ligands, in particular the ones that are based on a rigid N-heterocyclic core, is predisposed to coordinate in a meridional fashion. Negatively charged derivatives of these meridionally coordinating N-heterocyclic ligands satisfy all the criteria for PNP pincer scaffolds. Herein, these ligands and their coordination chemistry is reviewed from the perspective of coordination chemistry. For our discussion, ligands containing a protonated N-heterocycle (e.g. pyrrole- or carbazole-based PNP scaffolds) are to be distinguished from their counterparts that do not contain such an NH-functionality (e.g. pyridine- or triazine-based PNP scaffolds). Different synthetic methodologies for the preparation of PNP pincer complexes are presented and shown to often depend on the presence or absence of the aforementioned NH-proton. The different reactivity patterns of the resulting complexes are sub-divided into two categories, namely into metal-centered reactions and reactions that result in a chemical transformation at the metal and the ligand. The latter represent ligand-cooperative transformations, which often play a key role in catalysis, and are showcased by discussing selected applications in catalysis. It will become evident in this review that this relatively young research field is still emerging and far from reaching maturity. Finally, a brief overview on ligand/metal combinations that have not been explored to date is provided, to stimulate future research on PNP pincers featuring a central N-heterocycle.